Sloths of the Atlantic Forest in the sixteenth and seventeenth centuries - MOREIRA,DANIELLE O. (2016)
ABSTRACT Sloths were a curiosity item for Europeans in the 16th and 17th centuries, and several descriptions of them exist in bestiaries and texts of that time. Here, we assemble the descriptions and drawings of sloths from the travellers and naturalists of those centuries in the Brazilian Atlantic Forest. The sloth was a novelty to the European audience, and it was described in many strange and inaccurate ways: as a monster, a beast, or an odd child. It served as a source of admiration, amusement, and confusion among naturalists and travellers of the 16th and 17th centuries. We also raised the question about the identity of Carolus Clusius' sloth, a drawing published in Exoticorum libri decem (1605). We compared his drawing with earlier depictions and descriptions, from André Thevet (1516-1590) to George Marcgrave (1610-1644). We present evidence to validate the first drawing of the maned sloth, completed 206 years before the official taxonomic description.